PERANAN PURCHASING DALAM PENGADAAN BARANG DIHOTEL THE RITZCARLTON JAKARTA MEGA KUNINGAN - Putri, Gea Fitriannisa; Gulfira, Poeti Nazura; Priyandhini, Besty (Journal of Indonesian Tourism and Policy Studies, 2018)
This study discusses the process of material procurement of goods, the process of filing documents by staff purchasing, and obstacles experienced by staff purchasing during the procurement process. The method used in the writing of this final work is a field observation method where the authors participate directly to the field to see, research, and perform. The author also used interview methods to get a direct answer from industry players.